2015
DOI: 10.1080/03906701.2015.1078528
|View full text |Cite
|
Sign up to set email alerts
|

Theorising fatherhood, welfare and the decline of patriarchy in Japan

Abstract: This paper sets research perspectives on Japanese fathers within a broader review of welfare regime literature and gender theory to develop a historical perspective on fatherhood and work-life balance debates in Japan. The aim of the paper is to build on the comparative social policy and evidenced-based hypothesis that addressing men's social citizenship rights as fathers is the most effectual way to increase their involvement in childcare (Rush, 2015).The paper engages critically with classifications of Japan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Under Prime Minister Shinzo Abe's administration, bigger focus is put on the role of fathers in childcare. This era marks the awareness that fathers also play a role in childcare as shown by, among others, articles written by Michael Rush (2015) and MS Tingting Tan (2016).…”
Section: Patriarchy In Japanmentioning
confidence: 97%
“…Under Prime Minister Shinzo Abe's administration, bigger focus is put on the role of fathers in childcare. This era marks the awareness that fathers also play a role in childcare as shown by, among others, articles written by Michael Rush (2015) and MS Tingting Tan (2016).…”
Section: Patriarchy In Japanmentioning
confidence: 97%
“…Disappointingly, prior to the COVID-19 pandemic, there was an imbalance in the research evidence concerning the involvement of the mothers of LDHH as compared to involvement of the fathers. While studies by DesJardin and Eisenberg (2007), and Lara and Saracostti (2019) have elaborated on the contributions, involvement, and roles of mothers in the education of LDHH, the little research data available reveals less commitment and involvement of fathers in their children's education (Ricci & Hodapp, 2003;Rush, 2015). Studies during the last decade have reported an increase in the amount of time that fathers spend with their children (Crespi & Ruspini, 2015;Flouri, 2005;Pleck & Masciadrelli, 2004;Rice, 2017), but a recent study by Hernawati and Herawati (2020) notes that fathers' involvement in the education of their children is not rated very highly by mothers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some of these issues may be strongly intertwined with law and policy. Policy has a strong influence on how families and society organize work and family in daily practice (Gregory & Milner, 2008; Rush, 2015). For example, through policy on, and length of, paternity leave.…”
Section: Implications For Bpt Practicementioning
confidence: 99%